Affective Capitalism in Academia Revealing Public Secrets - Nehring, Daniel; Brunila, Kristiina (Policy Press, 2023)
Chapter 9 EPDF available Open Access under CC-BY-NC-ND licence. Drawing on affect theory and research on academic capitalism, this book examines the contemporary crisis of universities. With 11 international and comparative case studies, it offers a unique exploration of the contemporary role of affect in academic labour and the organisation of scholarship and explores diverse features of contemporary academic life, from the coloniality of academic capitalism to performance management and the experience of being performance-managed.